NGHIÊN CỨU TỔNG HỢP VÀ TÍNH CHẤT CỦA MỘT SỐ HỢP CHẤT CHỨA VÒNG 2-PIRAZOLIN - Hoan, Phạm Văn; Minh Phương, Đỗ Thị; Hùng, Hà Mạnh; Trung, Vũ Quốc (Vietnam Journal of Chemistry, 2012)
The reactions of some unsaturated a,b-ketones with hydrazines and some its derivatives were investigated. unsaturated a,b-ketones reacted with hydrazine derivatives RNHNH2 in acetic acid/sodium acetate to give 1-R-3,5-diaryl-2-pyrazolines. The reaction of unsaturated a,b-ketones with hydrazine, however, gave 1-acetyl-3,5-diaryl-2-pyrazolines. The structure of the obtained compounds were confirmed by IR, UV, NMR spectra. Photoluminescence of some compounds were also investigated.